(3LQjeI GeJfGY GdehXa GdYGe Yf JfajP GdCMcGe GdbVGFjI (B/ s - (3CMeO MSjf CHhRjO LGOh GdeQGSis; (3CSGeI MSfjf YHjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3Ef GdeTQY GdLfGFi GdeUQi CQGO Cf jSHZ GdMeGjI GdLfGFjI ddeMche dge GdMGFRjf Ydi MLjI GdCeQ GdebVi ai eQMdI JfajP GdCMcGe GdbVGFjI(B: (3GdeNJU HJfajPgG GdehXajf GdYGejjf GdeNGWHjf HgG(B: (3deG dgPg GdeQMdI ef GdNWhQI HecGf dJMbjb eUdMI CaQGO GdeLJeY(B: (3aSdhc GdehXa GdYGe GdeeJfY Yf JfajP GdCMcGe GdbVGFjI jHdZ bOQkG LSjekG ef GdeNGdaI GdUGQNI dbhGfjf GdOhdI(B: (3aVdkG Yf MeGjI SjGOI GdOhdI h bGfhfgG VO Ci eMGhdI ddfjd efgG(B. (3aJfGhdfG ai gPG GdHMK GdehXa GdYGe GdeNJU HGdJfajP(B: (3h ef ai Mceg ai GdJTQjY GdeUQi h GdaQfSi ef MjK TZd GdehXa ddhXjaI GdYGeI(B: (3h habG deG hQO HbGfhf GdNOeI GdeOfjI Qbe (B81 (3dSfI (B2016: (3ef MjK JMOjO GdebUhO HGdehXa GdYGe(B: (3h ef gh GdehXa GdeNJU HGdJfajP(B: (3habG deG LGA HGdeGOI GdKGfjI ef PGJ GdbGfhf(B: (3cPdc JWQbfG Gdi GdebUhO HGdehXa GdYGe ai GdbGfhf GdEOGQi GdeUQi h GdaQfSi ef MjK OGFejI GdhXjaI GdYGeI(B: (3h GdYed dOi eQab YGe JOjQg GdOhdI Yf WQjb GdESJZdGd GdeHGTQ aVdkG Yf GdJYjjf ef LgI eNJUI Jedc Pdc(B: (3CjVkG HGdebUhO HGdehXa GdYGe ai GdJTQjY GdLfGFi GdeUQi h GdaQfSi(B. (3Ke EfJbdfG Gdi GdJMOK Yf Qcfi LQjeI GeJfGY GdehXa GdYGe Yf JfajP GdCMcGe GdbVGFjI GdeGOi h GdeYfhi(B: (3habkG deG CTGQJ dg GdeGOI (B123/2 (3ef bGfhf GdYbhHGJ(B: (3h eG dgPg GdLQjeI ef YbhHg JeKdJ ai GdMHS h GdYRd ef GdhXjaI GdYGeIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B332-352s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdehXa GdYGe s; (3GdCQcGf GdYGeI dLQjeI GdGeJfGYs; (3LQjeI GeJfGY GdehXa GdYGe s; (3JYWjd JfajP GdCMcGe GdbVGFjI s; (3GdYbhHI GdebQQI dLQjeI GdGeJfGYs; (3GdCMcGe GdGLQGFjI dQaY GdOYhis; (3fWGb QaY GdOYhi GdLfGFjI ef MjK GdCTNGUs; (3GdJTQjY GdaQfSjs; (3GdEfPGQ GdbVGFjs; (3GdTQhW GdeaJQVI ddLQjeIs; (3bjhO hELQGAGJ JMQjc GdOYhis; (3GdVeGfGJ GdELQGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs